Oxidation of olefins employing mesoporous molecular sieves modified with copper - Cánepa, Analía Laura (2013)
M41S type nano-structured materials prepared with Cu contents varying from 1.2 wt% to 6.9 wt% were synthesized by the template ion exchange method to be used as potential catalysts in the reaction of - pinene oxidation with H2O2. The catalysts were evaluated in the test reaction of cyclohexene oxidation as a method of selecting the most active material. The material selected for the oxidation of a-pinene was the one with the highest content of Cu (7%, w/w) due to its high activity and selectivity to allylic oxidation products. A reaction mechanism was proposed in order to explain the obtained results. The a-pinene conversion was closed to 25% being verbenone the major product. The stability of the catalyst to the leaching of the active species and the possibility of recycling were checked. The results confirm that the Cu species are not leached during the reaction. Thus heterogeneous catalyst can be recovered and reused many times without loss in catalytic activity and selectivity.